Pelaksanaan Rehabilitasi Sosial Luar Panti dalam Mengentaskan Korban Penyalahgunaan Napza di Propinsi Bali - Sri Kuntari (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2013)
Various types of drugs flow through illegally to Indonesia, so that it can be categorized the state is in dangerousÂ condition. Indonesian position has been seen around the world as a state that used to be a place of consumers, then becomes a place of transit and drugs producer, proved by frequent findings of big scale drug producers in several place. The fact is supported by drug abuse data received by Supreme Court that the cases have increased 40 percent only in one year. The increase of drug abusers signs there is a need of an institution to rehabilitate ex drug victims. The government takes a role to help drugs victims through non-institutional social rehabilitation program. The goal of this research is to get a description on its program and to know the handicap and supporting factors of the program on lifting the victims from drugs addiction in Bali Province. This research is done descriptively, the informant (as data resources) are ex-clients and Bali Social Agence aparatus working for drugs victims rehabilitation program. Data are analyzed through quantitative technique. The research finds that the rehabilitation is implemented as non-institution regulation, and in the process of rehabilitation the victims are given social, mental, skills guidance and health check up. The sucsess of rehabilitation can be seen from the working togetherness between related agencies and non-governments organizations, and its continuity in guiding exvictim in Joint Business Group (Kube). The handicap is found in the lack of ex-victims working spirit, and their lives styles are difficult to be motivated to chance. There by, to increase clients enthusiasm to follow the rehabilitation activities, the kinds of skill given should be updated as market needs, so that kube can be developed and ex-clients will not relaps, it needs continuos monitoring.